Light‐Induced Surface Modification of Natural Plant Microparticles: Toward Colloidal Science and Cellular Adhesion Applications. (1st March 2018) - Tan, Ee‐Lin; Potroz, Michael G.; Ferracci, Gaia; Jackman, Joshua A.; Jung, Haram; Wang, Lili; Cho, Nam‐Joon
Abstract: Playing an instrumental role in the life of plants, pollen microparticles are one of the most fascinating biological materials in existence, with abundant and renewable supply, ultrahigh durability, and unique, species‐specific architectural features. Aside from their biological role, pollen microparticles also demonstrate broad utility as functional materials for drug delivery and microencapsulation, and increasingly for emulsion‐type applications. As natural pollen microparticles are predominantly hydrophobic, developing robust surface functionalization strategies to increase surface hydrophilicity would increase the range of colloidal science applications, including opening the door to interfacing microparticles with biological cells. This research investigates the extraction and light‐induced surface modification of discrete pollen microparticles from bee‐collected pollen granules toward achieving functional control over the responses elicited from discrete particles in colloidal science and cellular applications. Ultraviolet–ozone treatment is shown to increase the proportion of surface elemental oxygen and ketones, leading to increased surface hydrophilicity, enhanced particle dispersibility, tunable control over Pickering emulsion characteristics, and enhanced cellular adhesion. In summary, the findings demonstrate that light‐induced surface modification improves the functional properties of pollen microparticles, and such insights also have broad implications across materials science and environmental science applications. Abstract : Light‐induced surface modification of natural plant microparticles increases surface hydrophilicity for interfacial science and cellular applications. The modification of surface chemistry provides tunable control over particle wetting properties, emulsification characteristics, and particle/cell adhesion.